2022
DOI: 10.1002/wsb.1327
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter‐based immobilization of moose using butorphanol–azaperone–medetomidine

Abstract: Chemical immobilization is an important tool for the capture, study, and management of wildlife. Increased regulation of traditional opioids has necessitated a search for alternative drugs in wildlife capture. Butorphanol-azaperone-medetomidine (BAM) is one promising alternative that has been used in a range of taxa, though often on medium-size mammals using groundbased methods. We tested the efficacy of BAM via remote delivery from a helicopter in a wild population of moose (Alces alces shirasi) in northweste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This is consistent with previous observations that supplemental oxygen appears to counteract observed hypoxia with alpha-2 agonist and opioid combinations (Wolfe et al 2014; Lamglait et al 2021). Some researchers have reported that supplemental oxygen was not necessary with BAM use (Levine et al 2022); however, those authors considered an SpO 2 of <70% (or a “downward trend”) as their cutoff. We recommend that supplemental oxygen be provided for planned captures of moose immobilized with BAM to decrease the likelihood of potential adverse health outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous observations that supplemental oxygen appears to counteract observed hypoxia with alpha-2 agonist and opioid combinations (Wolfe et al 2014; Lamglait et al 2021). Some researchers have reported that supplemental oxygen was not necessary with BAM use (Levine et al 2022); however, those authors considered an SpO 2 of <70% (or a “downward trend”) as their cutoff. We recommend that supplemental oxygen be provided for planned captures of moose immobilized with BAM to decrease the likelihood of potential adverse health outcomes.…”
mentioning
confidence: 99%
“…Anecdotally, we believe terrain type and features may play a role in this variation. Other researchers have reported that moose routinely remained in sternal recumbency without assistance under the influence of BAM (Levine et al 2022). In either situation, researchers should be cognizant of recumbency and positioning in their capture procedures.…”
mentioning
confidence: 99%